Regional and inter‑regional DRIS norms for nutritional evaluation of Conilon coffee - Wadt, Paulo Guilherme Salvador; Dias, Jairo Rafael Machado (Pesquisa Agropecuaria Brasileira, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this work was to evaluate the performance of regional and inter‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">regional norms of the diagnosis and recommendation integrated system (DRIS) on the nutritional diagnosis of Conilon coffee (<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Coffea canephora<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">). Data on foliar contents of N, P, K, Ca, and Mg, obtained from 268 coffee crops from the states of Espírito Santo and Rondônia, Brazil, were used to define four sets of DRIS norms: three for specific conditions (regional norms), and one for all the tested conditions (inter‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">regional norms). Crops differed greatly as to management and environmental conditions. After the determination of the norms, the nutritional diagnoses obtained from them were confronted with each other. All the norms were effective in providing diagnoses to distinguish the nutritional patterns of the crops, both in the states of Espírito Santo and Rondônia. For the inter‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">regional DRIS norms, the means and standard deviations of the multivariate ratios between nutrients had intermediate values in comparison to those obtained for the sets of regional norms. No randomness was observed in the nutritional diagnosis provided by inter‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">regional norms, which had a great agreement level with the one provided by regional norms. Specific norms should be used only in the conditions in which they were developed, whereas generic norms have a wider applicability without jeopardizing the accuracy of the diagnosis.